The Haye Way podcast for Improving English listening skills A Conceptual Analysis - Afkari, Ahnif Adhhar; Priyatmojo, Arif Suryo (Journal of English Language and Education, 2025)
Listening skill is a crucial yet challenging aspect of English as a Foreign Language (EFL) learning, particularly for junior high school students with limited exposure to authentic spoken English. Although podcasts have been widely used in language learning, existing studies mainly focus on empirical outcomes, while conceptual analyses linking podcast characteristics to listening theories remain limited. This article aims to conceptually analyze The Haye Way Podcast as a medium for improving English listening skills. Using a conceptual research design, this study synthesizes theories of listening comprehension, meaningful and comprehensible input, and podcast-based learning. The analysis indicates that the podcast provides authentic yet accessible spoken input, familiar thematic content, and affective support that may facilitate listening comprehension. This article concludes that The Haye Way Podcast has theoretical potential as a supportive listening resource in EFL contexts and offers pedagogical insights for listening instruction.